Saikosaponin-d Attenuates Hashimoto's Thyroiditis by Regulating Macrophage Polarization. (8th November 2022) - Du, Peng; Xu, Jianbin; Jiang, Yanfei; Zhao, Jing; Gao, Chaoqun; Fang, Yudie; Yang, Xiaorong; Yang, Yan-ping; Zhang, Jin-an
Abstract : Objective . Hashimoto's thyroiditis (HT) is one of the most common clinical autoimmune diseases. Recent studies have found that HT pathogenesis is associated with macrophage polarization. Saikosaponin-d (SSd) is an active component in the Chinese medicine Bupleurum, which has anti-inflammatory and immunomodulatory effects. The purpose of this study was to verify the therapeutic effect of SSd on HT and to investigate the regulatory effect of SSd on macrophage polarization in HT. Methods . Network pharmacology analysis was used to predict the relevant targets and signaling pathways of SSd for HT treatment. The therapeutic effect of SSd on HT model mice and the effect on macrophage polarization were detected by animal experiment. Results . Network pharmacological analysis showed that SSd can alleviate HT against multiple targets such as IL-6 and IL-10 and can act on macrophage polarization-related signaling pathways such as MAPK and JAK-STAT signaling pathways. Animal experiments showed that SSd intervention attenuated the lymphocytic infiltration in thyroid tissues of HT mice (P = 0.044 ); SSd intervention reduced serum TPOAb antibody level in HT mice (P < 0.001 ); SSd adjusted M1/M2 imbalance towards M2-type macrophage polarization in the spleen of HT mice (P = 0.003 ); SSd inhibited the expressions of Th1-type cytokine IFN- γ and Th17-type cytokine IL-17 systemically and locally in the thyroid of HT mice (P < 0.05 ). Conclusion . SSd treatment can regulate Th1/Th2 and Th17/Treg imbalances and reduce the severity of HT in mice by promoting the polarization of M2 macrophages.